Kewarganegaraan dan Kemiskinan : Kebijakan Pemerintah dalam Mengatasi Kemiskinan di Kalangan Warga Negara Asing - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; M Aufa Mujtaba; Nur Azizah Choirun Nisa; Nanda Ambika Fatikasari (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Poverty among foreign nationals is an increasingly pressing global issue that is often overlooked in public policy. This study examines government policies designed to address poverty among migrants and refugees and their impact on their economic well-being. The main focus of the study is to highlight the effectiveness of different policy approaches that have been implemented in different countries and identify best practices that can be adapted to different national contexts. Through an analysis of existing policies in several countries, including Germany and Canada, and relevant case studies, the study finds that approaches based on social and economic integration, employment, and direct assistance can play a significant role in reducing poverty among foreign nationals. The results show that policies that involve collaboration between governments, non-governmental organizations, and local communities are often more effective in achieving the desired outcomes. This study aims to provide evidence-based recommendations for future development policies that are more inclusive and effective. In doing so, it is hoped that this study will contribute to improving the economic well-being of foreign nationals and assist governments in designing policies that are more responsive to the needs of this group.